2007
DOI: 10.1203/pdr.0b013e31809fda89
|View full text |Cite
|
Sign up to set email alerts
|

The Ocular Anomalies in a Cystinosis Animal Model Mimic Disease Pathogenesis

Abstract: Cystinosis is a lysosomal storage disorder characterized by abnormal accumulation of cystine, which forms crystals at high concentrations. The causative gene CTNS encodes cystinosin, the lysosomal cystine transporter. The eye is one of the first organs affected (corneal lesions and photophobia in the first and visual impairment in the second decade of life). We characterized the ocular anomalies of Ctns Ϫ/Ϫ mice to determine whether they mimic those of patients. The most dramatic cystine accumulation was seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…4 Cystine crystals are found first in the periphery of the cornea and then in the center. 33 Ctns Ϫ/Ϫ mice demonstrate similar ocular anomalies to patients, 14,34 and cystine crystals are also first found at the periphery of the cornea. In addition to the decreased cystine content, BMC transplantation led to a significant decrease in the number of mice with corneal cystine crystals (43% WT BMCs vs 86% of Ctns Ϫ/Ϫ BMCs; P Ͻ .05).…”
Section: Discussionmentioning
confidence: 66%
“…4 Cystine crystals are found first in the periphery of the cornea and then in the center. 33 Ctns Ϫ/Ϫ mice demonstrate similar ocular anomalies to patients, 14,34 and cystine crystals are also first found at the periphery of the cornea. In addition to the decreased cystine content, BMC transplantation led to a significant decrease in the number of mice with corneal cystine crystals (43% WT BMCs vs 86% of Ctns Ϫ/Ϫ BMCs; P Ͻ .05).…”
Section: Discussionmentioning
confidence: 66%
“…13,24 IOP measures in Ctns À/À mice were significantly higher compared to wild-type mice (see Table), reaching greater than 20 mm Hg in 5 of 54 eyes. In contrast, high-and low-HSPC engraftment in HPSC-treated Ctns À/À mice demonstrated decreased IOP compared to Ctns À/À mice, with no observed measures above 20 mm Hg (P ¼ 0.006, v 2 test).…”
Section: Eyesmentioning
confidence: 92%
“…11,13,14,18 To evaluate whether HSPCs prevent corneal atrophy in Ctns À/À mice, we measured the CCT in hematoxylin-stained eye sections, as described previously. 31 We found that the cornea of old Ctns À/À mice (approximately 13 months of age; n ¼ 4) was significantly thinner than in wild-type animals (n ¼ 4), an effect most apparent in the epithelial layer (Fig.…”
Section: Rescue Of Corneal Atrophy In Hspc-treated Ctnsmentioning
confidence: 99%
See 2 more Smart Citations